Substitution of manure for mineral P fertilizers increases P availability by enhancing microbial potential for organic P mineralization in greenhouse soil - Sun, Ruibo; Niu, Junfang; Luo, Bingbing; Wang, Xiaogai; Li, Wenyan; Zhang, Wenjie; Wang, Fenghua; Zhang, Chaochun; Ye, Xinxin (Frontiers in Bioengineering and Biotechnology, 2022)
The shortage of phosphorus (P) as a resource represents a major challenge for the sustainable development of agriculture. Manure has a high P content and is a potential substitute for mineral P fertilizers. However, little is known about the effects on soil P availability and soil microbial P transformation of substituting manure for mineral P fertilizers. In this study, variations in soil P availability and bacterial P mobilization were evaluated under treatment with manure as compared to mineral P fertilizers. In the greenhouse fruit and vegetable production system that provided the setting for the study, substitution of manure for mineral P (PoR treatment) resulted in a similar level of soil total P and a similar fruit and vegetable yield as compared to traditional fertilization, but a significantly increased level of soil available P. In addition, PoR treatment enhanced bacterial organic P mineralization potential and decreased inorganic P dissolution potential. These results demonstrate that manure application increases the availability of soil P primarily by enhancing soil microbial Po mineralization, indicating the potential feasibility of applying manure instead of mineral P fertilizers in greenhouse farming.